The Perceived Image of TransJakarta Bus Rapid Transit - Warman, Andri; Firdaus, Muhammad Iqbal; Rahmawati, Aisyah (STMT Trisakti, 2015)
Public transport services provided by Bus Rapid Transit TransJakarta has been launched by the local government of DKI Jakarta as a mass and rapid transport mode that can attract the users of personal vehicle to use this mode of transport. Although the passengers are increasing, but the condition has not reached the optimum level yet. This study is done as an attempt to map the image perceived by the users, either frequent users, occasional users, or non-frequent users. The image projected by the users will depend on the experience degree and information each individual has. The method used here is descriptive analysis and reduction factor to obtain the dimensions of image in the respondentsâ mind toward TransJakarta bus. The result shows five dimensions that construct the image, namely affective dimension (Eigenvalue = 5,488, or 26% of all variances), dimension of vehicle aspects (Eigenvalue = 1,794, or 8.5% of all variances), dimension of service characteristic (Eigenvalue = 1,635, or 7.8% of all variances), dimension of impact on the trip (Eigenvalue = 1,348, or 6.4% of all variances), and dimension of impact on the user/other people (Eigenvalue = 1,088, or 5.1% of all variances). Keywords: image, TransJakarta, Bus Rapid Transit, perception, transport